An enhanced C. elegans based platform for toxicity assessment - Xiong, Huajiang (Sci Rep, 2017)
There is a well-defined regulatory framework governing the approval of chemicals for use as pharmaceuticals or release into the environment. Toxicity assessment is thus a major hurdle in the compound discovery pipeline, currently involving large scale animal testing. The search for alternative testing platforms is therefore an important priority. We have developed a convenient, low cost assay utilising the nematode Caenorhabditis elegans, to rapidly assess both acute toxicity and developmental and reproductive toxicity (DART). However the worm is protected by a robust cuticle that forms a barrier to chemical uptake. We assessed mutants with altered cuticle properties to identify sensitized strains optimized for toxicity assays. Evaluating the trade-off between increased permeability and reduced fitness identifies bus-5(br19) as the most suitable strain for chemical exposure. We demonstrate the applicability of this assay for a range of chemicals with differing properties, including a modified exposure protocol for volatile or less soluble compounds. This work enhances the effectiveness of C. elegans for convenient toxicity assessment, which could contribute to a reduction in the use of vertebrates particularly at the crucial early stages of product development. Strains identified in this work will also enhance the sensitivity of C. elegans based drug discovery platforms.